2022
DOI: 10.1111/cga.12482
|View full text |Cite
|
Sign up to set email alerts
|

A case of 46,XY disorders of sex development with congenital heart disease caused by a GATA4 variant

Abstract: GATA4 is known to be a causative gene for congenital heart disease, but has also now been associated with disorders of sexual development (DSD). We here report a pathogenic variant of GATA4 in a 46,XY DSD patient with an atrial septal defect, identified by whole‐exome sequencing to be c.487C>T (p.Pro163Ser). This mutation resulted in reduced transcriptional activity of the downstream gene. When we compared this transcriptional activity level with other GATA4 variants, those that had been identified in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Finally, the presence of tetralogy of Fallot is surprising and was not reported elsewhere in association with a mutated SF-1. However, we could not exclude an additional genetic anomaly in other genes associated with DSD and/or tetralogy of Fallot, GATA4 and ZFPM2/FOG2 genes, for example ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the presence of tetralogy of Fallot is surprising and was not reported elsewhere in association with a mutated SF-1. However, we could not exclude an additional genetic anomaly in other genes associated with DSD and/or tetralogy of Fallot, GATA4 and ZFPM2/FOG2 genes, for example ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, 26 cases with 46,XY DSD due to the GATA4 gene have been reported until now ( Table 2 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Only five cases were raised as female.…”
Section: Discussionmentioning
confidence: 99%
“…CHD was found in five patients, and three cases of them had atrial septal defects. Yui Shichiri et al suggested that GATA4 activity is mostly deficient in patients with both cardiac defects and DSD than that observed in patients with only CHD [ 18 ]. This conclusion was derived by analyzing the expressivity of the p.Pro163Ser variant of GATA4 in five different patients with CHD of which only one also presented a DSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations